CAR T-Cell Therapy Predictive Response Markers in Diffuse Large B-Cell Lymphoma and Therapeutic Options After CART19 Failure - Caballero, Ana Carolina; Escribà-Garcia, Laura; Alvarez-Fernández, Carmen; Briones, Javier (Frontiers in Immunology, 2022)
Immunotherapy with T-cells genetically modified with chimeric antigen receptors (CARs) has shown significant clinical efficacy in patients with relapsed/refractory B-cell lymphoma. Nevertheless, more than 50% of treated patients do not benefit from such therapy due to either absence of response or further relapse. Elucidation of clinical and biological features that would predict clinical response to CART19 therapy are of paramount importance and eventually may allow for selection of those patients with greater chances of response. In the last 5 years significant clinical experience has been obtained in the treatment of diffuse large B-cell lymphoma (DLBCL) patients with CAR19 T-cells, and major advances have been made on the understanding of CART19 efficacy mechanisms. In this review, we discuss clinical and tumor features associated with response to CART19 in DLBCL patients as well as the impact of biological features of the infusion CART19 product on the clinical response. Prognosis of DLBCL patients that fail CART19 is poor and therapeutic approaches with new drugs are also discussed.